Effect of Artificial Intelligence Implementation and Product Innovation on Digital Marketing Strategy Effectiveness in Palopo City's Micro, Small, and Medium Enterprises - Ananda Ananda; Suhardi M Anwar; Muhammad Aqsa (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effect of artificial intelligence and product innovation on the effectiveness of digital marketing strategies among MSMEs in Palopo City. Methodology: A quantitative approach with a causal explanatory design was employed. The population consisted of MSMEs actively engaged in digital marketing. Using purposive sampling and the MoE formula, a sample of 96 respondents was obtained. Data were collected through questionnaires and analyzed statistically using SmartPLS 3. Results: The results show that artificial intelligence and product innovation directly have a positive and significant effect on the effectiveness of digital marketing strategies, both partially and simultaneously. Findings: The findings confirm that AI adoption and product innovation are key drivers of digital marketing effectiveness in the local MSME context. Novelty & Originality: This study offers novelty by examining AI and product innovation in the context of MSMEs in Palopo City, a region rarely explored in prior research on digital marketing. Conclusions: The results imply that the use of AI and product innovation can increase the effectiveness of digital marketing strategies for MSME products in Palopo City. Type of Paper: This paper is an empirical research paper.